Evaluation of Dietary Hempseed and Hempseed Oil on Performance, Egg Quality and Some Blood Parameters in Laying Hens after Peak Period - Bazdidi H; Afzali N; Hosseini-Vashan SJ; Ghiasi SE; Malekaneh M (Poultry Science Journal, 2016)
The aim of this study was to recognize the effects of dietary hempseed (HS) and hempseed oil (HO) on performance, egg quality and blood parameters of laying hens. A total of 320 Hy-line 55-weeks laying hens were randomly allotted to eight dietary treatments with five replicates (8 birds each). The experimental treatments were offered as a completely randomized design as follow: control group (no addition), four levels of HS (5, 10, 15, 20%), and three levels of HO (2, 4, 6%) added to the basic diet. The trial was performed for 12 weeks (3 four-weeks periods) started at the age 55 wk. Eggs were daily collected and weighed. Results showed that the highest egg production, egg mass and the lowest feed intake and feed conversion ratio were observed in birds fed 6% HO in diet (P< 0.05). With increasing the levels of HO from 4 to 6%, the Haugh unit significantly increased at the third period (P